an-Nadzariyyatu at-Tarbawiyyatu â€˜Inda Paulo Freire wa IrtibÄtuhÄ bi Taâ€™lÄ«mi al-Lughah al-â€˜Arabiyyah FÄ« Indonesia - Amrullah, Afif (IAIN Bone, 2023)
Hypothetically, this research argues that the teaching of Arabic as a second language in Indonesia should have a commitment to social justice. Thus, this research explores Paulo Freire's educational concept and considers how it relates to teaching Arabic itself. Paulo Freire helped usher in a new way of thinking about education and inspired an educational paradigm to focus more on injustice, oppression in education. Judging from Freire's thought, the educational aspect has a political dimension. This is because education aims at social transformation. This study uses library research methods to analyze the dimensions of Freirean pedagogy in teaching Arabic to foreign speakers. The results of this study are to provide understanding and suggestions for a new paradigm in teaching and learning Arabic for foreign speakers in Indonesia; According to the principles of Freirean pedagogy, Arabic teachers who are unable to respect students in their aesthetic and linguistic expressions violate basic ethical principles of the human condition. The researcher concludes argumentatively that this educational idea will definitely provide a good new tradition for the study of Arabic as a second language in Indonesia.